Fluorogenic displacement biosensors for PSA detection using antibody-functionalised quantum dot nanoparticles. Issue 9 (23rd December 2014) - Frascione, Nunzianda; Gooch, James; Abbate, Vincenzo; Daniel, Barbara
Abstract : Novel quantum dot conjugated immunosensors are presented for the accurate identification of seminal fluid in forensic casework. Abstract : Novel quantum dot conjugated immunosensors are presented for the accurate identification of seminal fluid in forensic casework. The production of a fluorescence signal upon the displacement of moderately bound quencher-labelled peptide analogues by Prostate Specific Antigen (PSA) overcomes many of the practical disadvantages associated with traditional lateral flow cartridge testing.